TiC-based coatings deposition using electric discharged plasma; Journal of Physics: Conference Series; Vol. 830 : Energy Fluxes and Radiation Effects 2016 - Rakhmatullin I. A. Ilyas Aminovich; Sivkov A. A. Aleksandr Anatolyevich; Gerasimov D. Yu. Dmitry Yurievich; Ivashutenko A. S. Alexander Sergeevich; Shanenkova Yu. L. Yuliya Leonidovna (Modification of materials with particle beams and plasma flows, 2017)
Title screen